Serafina and the splintered heart - Beatty, Robert, 1963- (Disney-Hyperion, 2018)
Serafina awakens in darkness and learns a terrible truth. She also learns that Biltmore Estate has changed in terrible ways and that a mysterious threat is moving towards it, endangering all she loves. Serafina races to come up with a plan to defend Biltmore--a plan that includes an unlikely ally.